"Black Children Are an Endangered Species": Examining Racial Framing in Social Movements. Issue 3 (3rd July 2018) - Luna, Zakiya
ABSTRACT: The "Endangered Species" anti-abortion billboard controversy in Atlanta in 2010 gained international attention and sparked lengthy discussion about the causes and consequences of black women's abortion rates and abortion in general. While abortion is typically presented as gendered phenomenon, race and class dimensions influence the contours of support and opposition to the issue. This case provides a unique opportunity to consider black social movements as black people led both sides of the billboard controversy and engaged particular authentic discourses. This article builds on the research on race frames to illuminate the (micro) processes of racial framing, the social movement organizations' implicit and explicit deployments of race in claims making. By examining how both sides engaged participants, opponents, and media, this article demonstrates how racial framing is an important tool for minority social movements with implications for other social movements and policy.